Synthesis of hydrazine containing piperazine or benzimidazole derivatives and their potential as a-amylase inhibitors by molecular docking, inhibition kinetics and in vitro cytotoxicity activity studies - ERDEM, SAFİYE (SPRINGER BIRKHAUSER, 2021)
The alpha-amylase is the main product of pancreas and is necessarily involved in the hydrolysis of carbohydrates into glucose so that it has been known to be a pioneer target for type 2 Diabetes mellitus (DM). Type 2 DM has no certain cure and the global increase in the cases of DM requires effective and extensive number of drug candidates. Drug discovery studies using organic biochemistry approaches are of important to describe novel compounds. This study aimed to reveal inhibitory potential of 13 novel compounds containing piperazine or benzimidazole moieties on alpha-amylase. The novel compounds were synthesized, structurally corroborated by various spectral analysis (FTIR, UV-Vis, H-1 NMR and C-13 NMR) and screened for anti alpha-amylase activity. Among the synthesized derivatives, compound 14 was found to be the most potent inhibitor of alpha-amylase having IC50 64.8 +/- 1.8 mu M. Inhibition types and K-i values of the most effective molecules (14 and 10a with different moieties) were further investigated. Molecular docking studies were conducted to correlate the outcome of in vitro biochemical kinetic assays and therefore rationalize the binding interactions. In vitro cytotoxicity studies on pancreatic cancer (AR42J) cells were then performed for compound14, and the compound was found to be more effective compared to the positive control, acarbose. Prediction of in silico ADME properties of all tested molecules were determined.
Keywords: Piperazine; Benzimidazole; alpha-amylase inhibition; Molecular docking; Cell culture; MICROWAVE-ASSISTED SYNTHESIS; PANCREATIC ALPHA-AMYLASE; CELL-CYCLE ARREST; CANCER CELLS; ANTIMICROBIAL ACTIVITY; BIOLOGICAL EVALUATION; DENSITY FUNCTIONALS; HYBRID MOLECULES; DRUG DESIGN; APOPTOSIS